Challenges and Prescriptions to Corporate Governance Issues Facing State-Owned Enterprises (SOEs): A Zimbabwean Perspective - Admire Mthombeni; Sifile Obert; Nyamudzodza Juet; Mutanda Bronson; Mishi Sydney (CV. Literasi Indonesia, 2023)
The main objective of the study was to determine the corporate governance challenges facing State-Owned Enterprises in Zimbabwe. In so doing the study sought to proffer solutions and prescriptions to the challenges. In this view, the study adopted a quantitative research approach in which the positivist philosophy was applied. A cross-sectional survey design was used in which data was gathered using a structured questionnaire. The target population consisted of top and middle management, board members, board chairpersons, and CEOs of SOEs found in Zimbabwe. Using the sampling procedure developed by Krejcie and Morgan (1970), a sample size of 351 individuals was determined. The research employed stratified random sampling for sampling respondents. SPSS version 23 was used to analyze quantitative data. The research established that Corporate governance challenges faced by SOEs in Zimbabwe include the bureaucratic nature of SOEs which causes inflexibility, political history of SOEs, poorly composed boards, inefficient and lack of transparency in the appointment of boards, limited board independence, and unstable economic conditions. The research recommends that authorities in the Office of the President and Cabinet from the Corporate Governance Unit or State Enterprises Restructuring Agency should organize more corporate governance training for Boards and other custodians of corporate governance in State Owned Enterprises.